Digital Transformation of Human Resources and Employee Performance: The The Role of HR Analytics and Digital Leadership - Aisyah Siregar; Willy Cahyadi; Cia Cai Cen; Limega Candrasa (Global Research Collaboration, 2026)
This study aims to examine the effect of Digital Human Resource Transformation on Employee Performance by incorporating HR Analytics as a mediating variable and Digital Leadership as a moderating variable within an integrated framework. A quantitative explanatory design was employed using a cross-sectional survey of 236 employees from organizations in North Sumatra, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess direct, indirect, and interaction effects. The results reveal that Digital HR Transformation significantly enhances HR Analytics, which in turn improves Employee Performance. Digital Leadership has a direct positive effect on performance and strengthens the relationship between HR Analytics and Employee Performance. Furthermore, HR Analytics partially mediates the relationship between Digital HR Transformation and Employee Performance, and this indirect effect becomes stronger under high levels of Digital Leadership. The findings highlight the importance of aligning digital HR systems, analytical capability, and leadership support to achieve sustainable employee performance. Organizations should complement digital HR investments with HR analytics development and digital leadership capability. This study is limited by its cross-sectional design and reliance on self-reported data from a single regional context, which may affect causal inference and generalizability.